QFD approach for quality improvement of a sustainable product-service system / Nur Indrianti, Devika Kumala and Tri Wibawa - -, Nur Indrianti; Kumala, Devika; WIbawa, Tri (Universiti Teknologi MARA Cawangan Sarawak, 2016)
Increasing awareness of the importance of services has given rise to the concept of product-service system where goods and services are sold as an integrated package to customers. On the other hand, the emerging sustainability concept has escalated the demand for sustainability for industries. Consequently, it is necessary to build strategies that lead the company to achieve sustainability goals while keeping competitiveness. Drawing on the necessity service and sustainability concept in the quality improvement of the product-service system, this study aims to develop a systematic design tool by filling the gap to the previous studies. We used Quality Function Deployment (QFD) approach by considering customer requirements (VoC) and stakeholder requirements (VoSt), instead of VoC only, based on the service and sustainability dimensions. We refer to the proposed QFD approach as QFDSPS. We introduce service productivity index (SPI) to measure the performance of the system. Thus, in the proposed methodology, the strategies for quality improvement were defined as subject to VoC, VoSt, and SPI. The methodology was implemented in a Javanese restaurant which meets the characteristics of a product-service system. The result shows that the proposed method can be implemented. The implications due to the implementation of the method are also discussed.